Allogenic bone graft for femoral defect augmentation in hip revision arthroplasty: A case series - Wirries, Nils (Orthop Rev (Pavia), 2020)
Cortical bone loss in revision hip arthroplasty requires an adequate stabilization to achieve a durable implant fixation. This case series shall illustrate possible indications for the use of allogenic grafts in revision hip arthroplasty. Twelve patients with femoral bone loss were treated with allografts. In addition to established clinical scores, the radiological follow-ups were analyzed for hints of implants loosening and the osteointegration of the allografts. After a mean follow-up of 3.0 years the mHHS was 61.3 points and the UCLA 3.8. One patient showed a non-progressive radiolucency around the hip implant. The osteointegration of all allogenic grafts happened on time. Up to the last follow-up no revision surgery of the hip implants and the associated femoral bone graft was observed. Allogenic bone grafts present a method for biological stabilization in situations of large femoral cortical bone defects in revision hip arthroplasty.